Immediate effects on adult drinkers of exposure to alcohol harm reduction advertisements with and without drinking guideline messages: experimental study. (27th February 2018) - Wakefield, Melanie A.; Brennan, Emily; Dunstone, Kimberley; Durkin, Sarah J.; Dixon, Helen G.; Pettigrew, Simone; Slater, Michael D.
Abstract: Aims: To compare the immediate effects on drinkers of television advertisements focusing upon short‐ versus long‐term harms with and without low‐risk drinking guidelines. Design: Between‐participants on‐line experiment, with random assignment to view: (a) alcohol product advertisements (ALC control); (b) advertisements unrelated to alcohol (NON‐ALC control); (c) advertisements featuring short‐term harms (STH) of alcohol; (d) advertisements featuring STH plus a STH guideline (STH+G); (e) advertisements featuring long‐term harms (LTH); or (f) advertisements featuring LTH plus a LTH guideline (LTH+G). Setting: Australia, 2016. Participants: A total of 3718 drinkers aged 18–64 years (48.5% male). Measurements: Post‐exposure likelihood that participants provided a correct estimate of drinking levels associated with short‐ and long‐term harms; post‐exposure intentions to avoid alcohol or reduce consumption. Findings: After exposure to STH+G or LTH+G advertisements, participants were more likely to estimate correctly rather than overestimate drinking levels associated with harm, compared with those exposed to STH ( P  < 0.001) and LTH advertisements without guidelines, respectively ( P  = 0.019) and ALC control (STH+G, P  < 0.001; LTH+G, P  < 0.001) and NON‐ALC control conditions (STH+G, P  < 0.001; LTH+G, P  = 0.011). Drinkers exposed to STH conditions were more likely to intend to reduce next‐week alcohol consumption than those exposed to ALC control (both P  < 0.001) and NON‐ALC control conditions (STH, P  = 0.001; STH+G, P  < 0.001); a similar pattern was observed for intentions to avoid alcohol. Drinkers exposed to LTH conditions were also more likely than drinkers exposed to ALC or NON‐ALC controls to intend to avoid and reduce alcohol in the next week. Additionally, drinkers exposed to LTH+G were more likely to intend to reduce drinking than those exposed to LTH advertisements without guidelines ( P  = 0.022). Response patterns for low‐ and high‐risk drinkers by condition were similar. Conclusions: Alcohol harm television advertisements increase intentions to reduce alcohol consumption among both low‐ and high‐risk drinkers. The addition of low‐risk drinking guidelines can enhance these effects for advertisements featuring long‐term harms and improve estimates of both short‐ and long‐term harmful drinking levels.